Pemberdayaan Masyarakat Melalui Pelatihan Eco-print dengan Pemanfaatan Tanaman Lokal di Gampong Meunasah Kulam, Aceh Besar - Wira Dharma; Saida Rasnovi; Muhammad Ridha Siregar (Universitas Syiah Kuala, 2025)
Community empowerment through eco-print training by utilizing local plants aims to improve the skills and knowledge of the community in processing natural materials into value-added products. The training focused on the eco-print technique, which is a natural printing method that uses the potential leaves and local plants to create unique designs on fabrics. By utilizing local resources, participants not only learn new skills, but are also expected to develop sustainable creative enterprises with cultural relevance. The program involves active participation from the community, allowing them to share experiences and knowledge by conducted hands-on workshops on the eco-print technique, as well as build business networks. The results of the training showed an increase in participants' abilities in eco-print techniques and understanding of the importance of environmental sustainability. Through this initiative, the community is expected to support the increase their income by facilitated collaboration and business network development among participants for long-term growth, preserve local plants, and contribute to cultural and environmental preservation.